Manajemen Modal Kerja Bagi Bisnis Perusahaan Di Era Digital - Arief yuswanto nugroho; Ari Nurcahyo Darmawan (JOURNAL KOPERASI DAN MANAJEMEN, 2023)
Purpose – The goal of this essay is to undertake a theoretical analysis of working capital management’s function in boosting profitability. And to research and keep each component of working capital in the best possible balance in order to help the business become more profitable. Design/methodology/approach – Research Techniques The approach taken in this study is descriptive research, which describes the findings of research descriptions that have been made based on the data in this study in order to develop a theory that can be used to explain, forecast, and manage a phenomenon. Data gathering methods that make data collection easier Findings – Through indicators and financial ratios connected to working capital, such as cash turnover and accounts receivable turnover, working capital must be correctly managed to ensure the smooth running of the company’s operational activities. Working capital management enables businesses to attain and boost earnings and profitability while also assisting them in decision-making. Consequently, the firm will continue to exist. Research limitations/implications – This study uses more subjective informants since it uses descriptive and qualitative methods, which poses a serious risk to the impartiality of the research conclusions. When you meet additional researchers with different personalities, the findings may vary since the researcher’s personality will affect the research’s conclusions. Originality/value – Working capital management is one of the most crucial facets of a complete company’s spending management, according to Munawir (Maria, 2008: 2). In this research, working capital has to be managed appropriately to ensure that the business’ operational operations operate smoothly and successfully. Working capital-related financial indicators and ratios, such as cash turnover and accounts receivable turnover, can help with this. The business will be able to boost its earnings and profitability by using working capital management.